(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
Proton beam therapy is a promising technique used to cure various types of cancer diseases in the human body. This technique can selectively damage cancer cells while leaving surrounding cells unaffected thereby minimizing collateral damage to the healthy cells. The position and the width of the cancerous cells are determined to calculate the energy required to destroy the affected cells. The energy loss to the damaged cells and other body parts is calculated separately with high accuracy. Computational analysis indicates that proton beams with energies of 46 MeV, 47 MeV, and 48 MeV effectively destroy localized cancerous cells of the ovary from the epithelial cells to the more invasive cancerous growth while proton beam energy range of 50 MeV to 89 MeV should be considered for the treatment of liver cancer of both the periphery tumours and tumours in the hilum. Transport of ions in matter (TRIM) data shows that more than 80% of proton energy is given off during ion bombardment at Bragg’s peak, while the remaining percentage is lost by phonon production and by recoils.